Antibodies to Plasmodium falciparum Glycosylphosphatidylinositols: Inverse Association with Tolerance of Parasitemia in Papua New Guinean Children and Adults - Boutlis, Craig S. (American Society for Microbiology, 2002)
Individuals living in regions of intense malaria transmission exhibit natural immunity that facilitates persistence of parasitemia at controlled densities for much of the time without symptoms. This aspect of immunity has been referred to as malarial “tolerance” and is thought to partly involve inhibition of the chain of events initiated by a parasite toxin(s) that may otherwise result in cytokine release and symptoms such as fever. Antibodies to the candidate Plasmodium falciparum glycosylphosphatidylinositol (GPI) toxin have been viewed as likely mediators of such tolerance. In this study, the relationship between antibodies to P. falciparum GPIs, age, and parasitemia was determined in asymptomatic children and adults living in Madang, Papua New Guinea. The prevalence and intensity of antibody responses increased with age and were lowest in children 1 to 4 years old with the highest-density parasitemias. In children of this age group who were tolerant of parasitemia during the study, only 8.3% had detectable immunoglobulin G (IgG) and none had IgM antibodies to GPI. This suggests that anti-GPI antibodies are unlikely to be the sole mediator of malarial tolerance, especially in children younger than 5 years. Following antimalarial treatment, clearance of parasitemia led to a fall in anti-GPI IgG response in children and adolescents within 6 weeks. As anti-GPI antibodies potentially play a role in protecting against disease progression, our results caution against the treatment of asymptomatic parasitemia and suggest that generation of a sustained antibody response in children poses a challenge to novel antitoxic vaccination strategies.